2015
DOI: 10.1371/journal.pone.0137170
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Wnt Signaling Pathway Components in Osteogenesis of Mesenchymal Stem Cells in Osteoarthritis Patients

Abstract: IntroductionOsteoarthritis (OA) is characterized by altered homeostasis of joint cartilage and bone, whose functional properties rely on chondrocytes and osteoblasts, belonging to mesenchymal stem cells (MSCs). WNT signaling acts as a hub integrating and crosstalking with other signaling pathways leading to the regulation of MSC functions. The aim of this study was to evaluate the existence of a differential signaling between Healthy and OA-MSCs during osteogenesis.MethodsMSCs of seven OA patients and six heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…The most common conservative management of OA is by intra-articular injection: in recent times, traditional products such as corticosteroids and hyaluronic acid have been flanked by novel therapies based on immunomodulatory molecules and also on “autologous” derivatives such as PRP and MSCs that have the potential advantage of minimizing side effects due to their autologous nature [ 52 ]. Although limited evidence suggests that these biologic products could exert a modulation on the Wnt pathway [ 3 , 45 , 46 , 53 ], further studies are needed to understand which mechanisms are involved in Wnt-pathway modulation and how to take full advantage of PRP and MSCs concentrate in the control of OA progression. These powerful biologic products can be regarded as a reservoir of many bioactive molecules: understanding their role and the pathways they can influence will open the possibility of manipulating these products to obtain “autologous” drugs with specific biologic actions within the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The most common conservative management of OA is by intra-articular injection: in recent times, traditional products such as corticosteroids and hyaluronic acid have been flanked by novel therapies based on immunomodulatory molecules and also on “autologous” derivatives such as PRP and MSCs that have the potential advantage of minimizing side effects due to their autologous nature [ 52 ]. Although limited evidence suggests that these biologic products could exert a modulation on the Wnt pathway [ 3 , 45 , 46 , 53 ], further studies are needed to understand which mechanisms are involved in Wnt-pathway modulation and how to take full advantage of PRP and MSCs concentrate in the control of OA progression. These powerful biologic products can be regarded as a reservoir of many bioactive molecules: understanding their role and the pathways they can influence will open the possibility of manipulating these products to obtain “autologous” drugs with specific biologic actions within the joint.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wnt-5A plays an essential role in IL-1β-mediated cartilage destruction 39 . Other evidence suggested that the genesis of SANFH is closely connected with its degradation and that of its secondary cascade target genes related to osteogenesis, angiogenesis, and adipocyte 40 42 . In the present experiment in vivo , PDTC administration blocked NF-κB activation, relieved inflammatory response and necrosis incidence, and upregulated the Wnt pathway and subsequent osteogenesis and angiogenesis concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt family of highly conserved secreted glycoproteins is rich in cysteine residues and controls not only the vital developmental processes of cell fate and polarity but also some cell maintenance processes. In humans, more than 19 Wnts, 10 FZD receptors, and 2 co-receptors (LRP-5, LRP-6) have been identified so far (Tornero et al, 2015 ). Among several Wnt signaling pathways, the Wnt/β-cat dependent (canonical) pathway has been well-characterized (Kim J. H. et al, 2013 ).…”
Section: Regulators Of Bone Formation and Resorptionmentioning
confidence: 99%